ANALISIS KESALAHAN DALAM MENJAWAB SOAL MATERI SEGIEMPAT DAN SEGITIGA PADA MASA PANDEMI COVID-19 BERDASARKAN TEORI NEWMAN BAGI SISWA SMP KELAS VIII - Dewi Kusumawati; Anik Yuliani (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
During the COVID-19 pandemic, learning is carried out online, including learning mathematics. Mathematics education is one of the fields of study that is important to study one of the materials in it, namely the material of quadrilaterals and triangles. However, several studies show that this material is still difficult to understand so that students have difficulty in answering questions about quadrilaterals and triangles. This study aims to analyze students' errors in answering questions about quadrilateral and triangle problems based on Newman's theory. This study uses a qualitative descriptive method. The research subjects were 20 students of SMPN 1 Sindangkerta. Data analysis techniques are divided into three steps: data reduction, presentation of data, and conclusions. The results showed that the mistakes that students made when completing the quadrilateral and triangle material problems were mostly at the skill stage and the final answer stage. Online learning and methods of delivering quadrilateral and triangle material by the teacher also cause students to not understand the material of rectangles and triangles so that students make mistakes when working on quadrilateral and triangle questions.